Ethical Framework for Iot in People Analytics: Risks and Opportunities - Mr. Nishant Gaur; Dr. Vikas Gupta (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Purpose: This research studies the ethical perspective concerning internet of things (IoT) placement in People Analytics. To provide researchers and professionals with ethical framework for IoT (internet of things) in people analytics. .Also to identify associated risk and opportunities. Design/methodology/approach: Initially, the applicability of Chuck Huff’s original Personality, Integration of morality, Moral Ecology and skills Model (PRIMES) is studied from context of IoT in people analytics. Secondly consideration of ethical issues in addition to PRIMES model are proposed based on limited scope of PRIMES in IoT and people analytics. Findings: The original PRIMES Model can be utilized in initial stages as ethical guiding framework for individuals employed in personnel department but it lacks coverage of ethical issues from perspective of IoT in people analytics. To address the ethical dimensions from IoT in people analytics viewpoint, additional ethical issues are addressed. Research limitations: The novel ethical framework for IoT in people analytics required further authentication and validation along with empirical testing in continuously emerging IoT and people analytics ecosystem. Implications: Considering the paucity of ethical frameworks in emerging area of IoT in people analytics, this study provides the ethical model in the area of IoT in people analytics for the researchers and practitioners. This framework can further be tested and used practically and can also be considered for theoretical development. Originality/Value: There is apparent deficiency of ethical norms in area of IoT in people analytics, this study contributes to the area by providing extended PRIMES Model as a preliminary ethical framework for IoT in people analytics.